FREE TIME AND LIFE QUALITY: A METALLURGICAL COMPANY CASE (Fiep Bulletin - online, 2015)
This research aimed to discuss the workers' free time of a in the city of Castro, Paraná State, Brazil. It also aimed to establish a relation between the activities performed during this period and Life Quality at Work. It is an applied research under a firstly qualitative approach and descriptive, for its objectives. It was undertaken as a survey and it was used questions form to gather the data. Norbert Elias and Eric Dunning theory oriented the discussions about free time. Discussions about Life Quality at Work were based on proposals from Limongi-França Thought Schools and on the theoretical model proposed by Walton. It was observed that during the workers' free time there are predominantly routine activities that are less pleasurable than typical leisure activities. It was brought to a conclusion that, among actions searching Life Quality at Work, several activities have close relation with the workers' free time.
Keywords: life quality; life quality at work; free time.